Standardization of the process of smelting for sands with self-forgeling resins in the Military Industry Santa Bárbara Factory - Carvajal-Fernández, Lina Consuelo; Suárez-Díaz, Laura Melisa (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2014)
This article describes the standardization of the smelting process for sands with self-forgeling resins in the Military Industry Santa Barbara Factory. The molding process was studied in the Smelter for six months, to set standards for workforce and raw materials, so that would allow truthfully evaluate the costs per kilogram of casting. 41 pieces of civil and military sectors throughout the development of the project were worked. Finally both standards were evaluated, labor as raw material for different parts, with results was evidenced improved process, essentially in workforce, while in raw material standards did not show significantly change, in this case is corroborated that existing ones are applicable to the process